Augmented reality based android application for introduction of pneumatic hydraulic components - Yuwono Indro Hatmojo; Christin Elisabet Panjaitan; Satria Muhammad Azis; Vando Gusti Al Hakim; Dwi Ratnawati (University of Muhammadiyah Malang, 2024)
This study focuses on the utilization of augmented reality (AR) to enable comprehensive visualization of objects. Its primary objective is to develop and evaluate an AR application as a medium for introducing pneumatic hydraulic components. The research method employs a development research approach, following the assessment, design, development, implementation, and evaluation steps proposed by Lee and Owens. The feasibility of the product is determined through various assessments, including black box testing, validation by media experts, validation by content experts, and evaluation of initial user response. The outcome of this study is application software incorporating AR technology for the purpose of introducing pneumatic hydraulic components, along with a corresponding workbook. Whereas the application is compatible with the Android operating system and utilizes QR codes as markers for augmented reality objects, which are conveniently included within the workbook. Performance testing reveals that all application functions perform exceptionally well according to black box testing. Furthermore, the content expert feasibility assessment yields results categorized as “Good,” while both the media expert feasibility and initial user response tests indicate “Very Good” outcomes.